1995
DOI: 10.1111/j.1476-5381.1995.tb15866.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of protein kinase C in the delayed cytoprotection following sublethal ischaemia in rabbit myocardium

Abstract: Rabbit hearts were preconditioned with four 5 min coronary artery occlusions 24 h before 30 min coronary occlusion with 120 min reperfusion. Preconditioning significantly reduced the percentage of myocardium infarcting within the risk zone from 49.1±4.3% to 31.8±3.5% (P<0.05). When the protein kinase C (PKC) inhibitor, chelerythrine, was administered just before preconditioning, the delayed protection against infarction 24 h later was abolished. We conclude that the delayed cytoprotective response associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(73 citation statements)
references
References 10 publications
4
67
0
2
Order By: Relevance
“…We showed that IH-induced cardioprotection was abolished when chelerythrine was infused before ischemia. This is in accordance with other studies which have shown, using chelerythrine, a role for PKC in mediating delayed ischemic [13] and pharmacological [26] PC. However, the implication of other kinases can not be excluded since chelerythrine has been reported to affect some of them [27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We showed that IH-induced cardioprotection was abolished when chelerythrine was infused before ischemia. This is in accordance with other studies which have shown, using chelerythrine, a role for PKC in mediating delayed ischemic [13] and pharmacological [26] PC. However, the implication of other kinases can not be excluded since chelerythrine has been reported to affect some of them [27].…”
Section: Discussionsupporting
confidence: 93%
“…In particular, the first demonstration of a role for PKC in delayed PC, was from Yamashita and colleagues who demonstrated that staurosporine, a PKC inhibitor, could prevent in vitro the acquisition of this phenomenon in hypoxic preconditioned rat cardiomyocytes [12]. Subsequently, it was observed in the rabbit, that the delayed protection following ischemic PC is abolished in vivo by chelerythrine (Chel), another PKC inhibitor [13]. The first aim of the present study was to assess whether the IH-induced reduction in infarct size is mediated and/or triggered by PKC (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that A 1 AR activation induces delayed protection in the rabbit heart. 4,6 This protection was attributed to the activation of protein kinase C (PKC) 10 and opening of the K ATP channel. 6,11 In the present study, we have shown a novel mechanism of A 1 AR-induced delayed cardioprotection in the isolated perfused mouse heart.…”
Section: Salient Findingsmentioning
confidence: 99%
“…Stimulation of Ն1 of these receptors activates the signaling pathway, which involves activation of phospholipase C and/or D, 15,16 production of diacylglycerol, and the resultant activation and subcellular distribution of Ն1 of the 12 known isoforms of PKC. 17 Baxter et al 10 suggested that a PKC signaling pathway may link the activation of adenosine receptor to the delayed cytoprotection that is observed many hours later. Their data demonstrated that chelerythrine, a specific PKC inhibitor, blocked delayed cardiac protection induced by ischemia in rabbit heart.…”
Section: Zhao Et Al Inos and Adenosine-induced Delayed Protectionmentioning
confidence: 99%
“…Some of the mechanism that are being studied include expression of heat shock protein (HSP70), alterations in the activity of superoxide dismutase, induction of inducible nitric oxide synthase, and involvement of PKC. 221,[223][224][225] Recently, Bolli et al showed that brief episodes of ischemic preconditioning can protect the porcine and rabbit heart from an episode of stunning 24 hours or more after the preconditioning episode 226 and that this protection is triggered by the generation of oxyradicals 227 and nitric oxide. 228 In addition, they demonstrated that in the conscious rabbit, the delayed protection against infarction is also triggered by the generation of nitric oxide during the initial preconditioning ischemia.…”
Section: Second Windowmentioning
confidence: 99%